PO 18124 - Large orthopedic surgery and its correlation with Cockett syndrome: a case report - Marum Bachir, Raffael; Asaumi, Inácio Diogo; Lo Turco, Donato; Rodrigues Fernandes, Clariana Casali; Luiz Kiyan, Fábio (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Cockett syndrome (CS) is characterized by compression of the left common iliac vein by the right common iliac artery against the spinal wall, causing obstruction of left lower limb (LLL) blood flow. The clinical condition is mainly manifested by pain and edema of the LLL and, in more severe cases, even by left iliofemoral venous thrombosis. It is already well established in the literature that in cases such as Cockett syndrome, orthopedic surgeries also corroborate the occurrence of deep vein thrombosis (DVT), mainly by the positioning and manipulation of the limb during the intervention; by the continuous reaction secondary to the use of cement; by significant blood loss; by postoperative (PO) edema; and by the mobility limitations PO. Case report: A 42-year-old patient complained of left foot pain and repetitive sprains for 2 years. After a complete physical examination indicating a cavovarus foot and a pointed hindfoot, an AP and profile radiograph of the limb was requested, which revealed data compatible with a foot cavity. The nuclear magnetic resonance demonstrated the necessity for cavo foot correction surgery and reconstruction of the structure of the ankle. The patient was classified as ASA 1 and had no indication for prophylaxis for DVT according to the Hospital Protocol. The surgical procedure occurred without intercurrences, and the patient was discharged in good general condition in the 2nd PO with guidelines and prescriptions. The patient returned to the foot clinic on the 7th PO complaining of abrupt pain in the LLL, accompanied by edema, hyperemia and cyanosis of the limb. A Doppler ultrasonography was performed, which detected extensive thrombosis of the iliac vein and compression of the same by the contralateral iliac artery, raising the hypothesis of CS. In the present paper, the exam images, surgery, PO and evolution for the DVT will be presented and discussed, as well as the resolution of this condition through endovascular surgery with angioplasty and stent implantation. Conclusion: CS and orthopedic surgeries are, in isolation, important risk factors for the development of DVT and, above all, when overlapped, they increase this risk exponentially. Endovascular surgery with angioplasty and stent implantation is the main form of treatment, presenting excellent clinical results.